Empreendedorismo, inteligência competitiva (IC) e a competência em informação (CoInfo) como dimensões estratégicas nas startups: estudo de caso da “Inova CPS” - Leite, Luciana Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Em ambientes mercadológicos competitivos e complexos, as startups são modelos de negócios que atuam para detectar e antecipar-se às oportunidades ainda não alcançadas por outras organizações e buscam apoio nos ecossistemas de inovação para aprender, se desenvolver e alcançar seus resultados. Elas atuam em ambientes de extrema incerteza e são dependentes de informações de mercado, sugerindo-se que a informação seja um elemento indissociável de suas estratégias. Nesse sentido, se faz necessário que esses modelos de negócios sejam subsidiados por informações estratégicas e inteligentes e que se faça presente a competência em informação a fim de alcançarem vantagens competitivas. Esta tese tem como objetivo identificar e demonstrar a inter-relação entre o Empreendedorismo, a Inteligência Competitiva (IC) e a Competência em Informação (CoInfo) e seu papel estratégico nas ações desenvolvidas nos ambientes de criação de startup, que estejam apoiadas no Programa Inova CPS. Para isso apresenta como procedimentos metodológicos uma revisão teórica junto à literatura sobre os temas: Empreendedorismo, Inteligência Competitiva e Competência em Informação, a fim de se construir um referencial teórico de apoio ao desenvolvimento de estudo de caso junto à Agência Inova Centro Paula Souza – Inova CPS, de modo a identificar e demonstrar a inter-relação entre esses temas, considerando-se o seu papel estratégico nas ações desenvolvidas nos ambientes startup, que estejam apoiadas na “Agência Inova CPS”, especificamente as ações traçadas e desenvolvidas na Escola de Inovadores, a partir da inter-relação dos Padrões de Competência em Informação de Belluzzo, com o Modelo de Inteligência Competitiva de Cinco Fases de Angeloni e outros., estabelecidos por Santos. Os resultados evidenciam a inter-relação entre Empreendedorismo, Inteligência Competitiva e Competência em Informação e como ela pode ser aplicada a favor da aprendizagem de empreendedores startups, em especial, no âmbito da Agência Inova CPS, porém, aplicável com adequação a outros contextos organizacionais similares, de modo a auxiliar na formulação de modelos de negócios inovadores. Como contribuição, ao final, propõe-se a apresentação da “Matriz Referencial para Criação de Oportunidades de Melhoria e de Otimização da Competência em Informação para a Sociedade Inovadora”, com o apoio dos princípios e abordagens que envolvem o Empreendedorismo, Inteligência Competitiva e demonstrando o papel central que envolve a CoInfo no processo de construção de modelos de negócios que são apoiados nesses temas, possibilitando sua assertividade quanto às necessidades das organizações contemporâneas, em especial aquelas que são consideradas como sendo startups.

In competitive and complex market environments, startups are business models that act out to detect and anticipate opportunities not yet reached by other organizations and they seek support in innovation ecosystems to learn, develop and achieve their results. They operate in environments of extreme uncertainty and are highly dependent on market information, suggesting that information is an inseparable element of their strategies. In this sense, it is necessary that these business models are supported by strategic and intelligent information and that information competence is present in order to achieve competitive advantages. This thesis aims to identify and demonstrate the interrelationship between Entrepreneurship, Competitive Intelligence (CI) and Information literacy (CoInfo) and its strategic role in the actions developed in startup creation environments, which are supported by the Inova Program. CPS. For this, it presents as methodological procedures a theoretical review with the literature on the themes: Entrepreneurship, Competitive Intelligence and Information literacy , in order to build a theoretical framework to support the development of a case study with Agency Inova Centro Paula Souza – Inova CPS, in order to identify and demonstrate the interrelationship between these themes, considering their strategic role in the actions developed in startup environments, which are supported by the “Agency Inova CPS”, specifically the actions outlined and developed at the School of Innovators, based on the interrelationship of Belluzzo's Information literacy Standards, with Angeloni's Five-Phase Competitive Intelligence Model and others, established by Santos. For this, it presents as methodological procedures a theoretical review with the literature on the themes: Entrepreneurship, Competitive Intelligence and Information literacy, in order to build with a theoretical framework to support the development of a case study with Agency Inova Centro Paula Souza – Inova CPS, in order to identify and demonstrate the interrelationship between these themes, considering its strategic role in the actions developed in startup environments, which are supported by the "Agency Inova CPS", specifically the actions outlined and developed at the School of Innovators, based on the interrelationship of Belluzzo's Information literacy Standards, with Angeloni's Five-Phase Competitive Intelligence Model and others, established by Santos. The results show the interrelationship between Entrepreneurship, Competitive Intelligence, and Information literacy and how it can be applied in favor of startup entrepreneurs learning especially within the scope of Agency Inova CPS, however, it is applicable with adaptation to other similar organizational contexts, in order to contribute to innovative business models formulation. As a contribution, it is proposed the presentation of the "Reference Matrix for Creating Improvement Opportunities and Optimization of Information literacy to the Innovative Society", with the support of principles and approaches that involve Entrepreneurship, Competitive Intelligence and it is demonstrated the central role which involves CoInfo in the process of building business models that are supported on these themes, enabling its assertiveness regarding the needs of contemporary organizations, especially those ones considered to be startups.
Entrepreneurship, competitive intelligence (CI) and information literacy (CoInfo) as strategic dimensions in startups: case study of “Inova CPS”
Keywords: Empreendedorismo; Inovação; Competência em informação; Inteligência competitiva; Startups; Entrepreneurship; Innovation; Competitive intelligence; Information literacy